Rejection Sensitivity, Urgency, and Interpersonal Difficulties in Young Adults - Asad, Vaniya; Majeed, Saima (Pakistan Journal of Humanities and Social Sciences, 2025)
The present study aimed to find the relationship between Rejection Sensitivity, Urgency (Negative and Positive), and Interpersonal difficulties in Young Adults. A purposive sample of 350 Young Adults (Men=175, Women=175) was approached from public and private universities of Lahore, Pakistan. Three scales were applied to assess the variables, Rejection Sensitivity (ARSQ), Positive and Negative Urgency subscales of the UPPS-P Scale, and Interpersonal Difficulties (Interpersonal Problems Circumplex IRT). Through statistical analyses, including Pearson correlation, multiple regression analysis, and t-test, the study determined the correlation, prediction, and gender differences in these psychological constructs. The results concluded that Rejection Sensitivity did not have a significant relationship with Interpersonal difficulties, but Urgency had a significant relationship with Interpersonal difficulties. Results indicated that among socio-demographic variables family systems proved a significant positive predictor of interpersonal difficulties. Similarly, Urgency also proved a significant predictor of Interpersonal Difficulties while Rejection Sensitivity did not. There was a gender difference observed in Rejection Sensitivity only that showed women scored higher than men. This research will help offer a deeper understanding of the relationship between these variables and help in aiming to contribute to mental health outcomes and overall well-being of young adults.